Analysis of a flat plate collector for hot water domestic use - a sensitivity study. (August 2016) - Stanciu, C; Stanciu, D; Gheorghian, A; Șoriga, I
Abstract: The paper presents the study of a flat plate collector (FPC) used to heat water for domestic use in stationary operation. A comparison is provided between the cases of constant and time-dependent water circuit, in clear sky conditions. Numerical results emphasize the hot water temperature obtained with a given FPC area for a certain value of the mass flow rate. Imposing both the mass flow rate and hot water temperature, the minimum required area of the FPC can be determined. The computations are based on energy and mass balance equations. Steady state is obtained after three days of continuous operation.